TANGGUNG JAWAB APARAT DAN KUALITAS PELAYANAN TERHADAP TINGKAT KEPERCAYAAN MASYARAKAT KABUPATEN OGAN KOMERING ULU SELATAN - Trihandayani, Zaleha (Jurnal Ilmu Manajemen, 2013)
This research has an eye to know the affection from responsibility of government officer and quality of service, to influence trust of society and government. The research design which is used contains of questionnaire tooffice and client counted 108 respondents. The result of answer is analysed statistically by using moment product with pearson which is operated with SPSS 16 for Windows. The result of this research indicates that there is a correlation among responbility of government officer and quality of service, to influence trust of society and government with F – Count is 47.859 meaning bigger than F – Table with trust storey; level 99% that is 4,79. Thereby Ho refused and Ha accepted by its meaning. There is a positive correlationamong responbility of government with hand in glove correlation storey level. R2 (determination) reside at number 46,7% its meaning the percentage isaffecting among responbilty of government officer and quality of service, to influence trust of society and government. It is counted 53,3% the rest influenced by other factor which don’t be commented in this research while equation had this research is Y = 16,860 + 0,523.X1 + 0,347 X2..